2017
DOI: 10.1186/s12915-016-0343-5
|View full text |Cite
|
Sign up to set email alerts
|

Surface attachment, promoted by the actomyosin system of Toxoplasma gondii is important for efficient gliding motility and invasion

Abstract: BackgroundApicomplexan parasites employ a unique form of movement, termed gliding motility, in order to invade the host cell. This movement depends on the parasite’s actomyosin system, which is thought to generate the force during gliding. However, recent evidence questions the exact molecular role of this system, since mutants for core components of the gliding machinery, such as parasite actin or subunits of the MyoA-motor complex (the glideosome), remain motile and invasive, albeit at significantly reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
227
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(256 citation statements)
references
References 61 publications
(130 reference statements)
28
227
1
Order By: Relevance
“…By 48 hr onwards, no F-actin structures could be observed and Cb-Halo was completely cytosolic, as expected due to cytosolic expression of this reagent (Figure 6B). The loss of filaments within the act1 cKO over-time follows the down-regulation of ACT1 in act1 cKO, indicating a polymerisation mechanism similar to eukaryotic actins (Whitelaw et al, 2017). To exclude a role of host cell actin in the formation of the inter-parasite connections, we treated infected host cells with the actin-disrupting drug latrunculin A, which specifically inhibits polymerization of host cell, but not parasite, actin (Hegge et al, 2010; Whitelaw et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By 48 hr onwards, no F-actin structures could be observed and Cb-Halo was completely cytosolic, as expected due to cytosolic expression of this reagent (Figure 6B). The loss of filaments within the act1 cKO over-time follows the down-regulation of ACT1 in act1 cKO, indicating a polymerisation mechanism similar to eukaryotic actins (Whitelaw et al, 2017). To exclude a role of host cell actin in the formation of the inter-parasite connections, we treated infected host cells with the actin-disrupting drug latrunculin A, which specifically inhibits polymerization of host cell, but not parasite, actin (Hegge et al, 2010; Whitelaw et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study suggested that the polymerization process of apicomplexan actin needs to be reinvestigated, as heterologously expressed apicomplexan actin, the basis for many of the previous studies, is incorrectly folded (Olshina et al, 2016). Furthermore, it was demonstrated that conditional deletion of act1 in T. gondii results in complete abrogation of known actin functions, long before G-actin levels are fully depleted, suggesting that in vivo the formation of F-actin depends on a critical monomer concentration (Whitelaw et al, 2017). This raises concerns about previous studies of actin polymerization kinetics based on mis-folded actin.…”
Section: Introductionmentioning
confidence: 99%
“…The conserved, short single-headed myosin heavy chain myosin A (MYOA), was then identified in T. gondii as the motor that was able to generate the rearward traction force necessary for motility, entry into, and egress from, host cells 48 . The composition and molecular details of the glideosome have been elucidated in more detail and discovered, respectively [49][50][51][52] , and the importance of the glideosome in motility and invasion has been assessed further 23,25,26,53,54 (Supplementary information S6 (table)). …”
Section: The Glideosome Machinerymentioning
confidence: 99%
“…Remarkably, tachyzoites that lack TgMYOA could still be propagated in culture, although their lytic cycle was severely impaired 23 . A model based on retrograde membrane flow has been proposed to account for the residual motility 25,26 . However, a probable explanation is the functional redundancy and parasite adaptation conferred by the presence of a second myosin heavy chain, TgMYOC 53 .…”
Section: Conoidmentioning
confidence: 99%
See 1 more Smart Citation